Perilaku Impulse Buying Muslimah Indonesia: Studi Kasus Pembelian tidak Terencana Produk Woman Fashion melalui Pembelian Online - Ika Yunia Fauzia; Nurchlis Setiawan; Shinta Setia (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Impulse buying for buying things behavior known as unplanned purchase behavior often that spread to everyone.There is no exception among Muslim women, often stuck to make purchases that are not planned on products woman fashion online. This is because of the ease of online shopping procedure in making a woman could has the deal of buying the things, without having to get out of the door of his home. By using qualitative methods, then this researchl concerned to discuss how the behavior of impulse buying is done by the Muslim Indonesia through online purchase. This research useed the analysis of case studies, with the observation, interviewing and documenting data from fifty informants from several cities in Indonesia. This research resulted several things related to how the woman of fashion moving behavior of impulsive purchases, backgrounds and types of Muslim women who make purchases are impulsive, and lastly the shifting trend Muslim perpetrators impulse buying, being a Muslimah dropshipping way of the online sellers or other ways